The African Americans [videorecording (DVD)] : many rivers to cross - Gates, Henry Louis, Jr (PBS Distribution, 2014)
Explore with Professor Henry Louis Gates, Jr., the evolution of the African-American people, as well as the multiplicity of cultural institutions, political strategies, and religious and social perspectives they developed-forging their own history, culture and society against unimaginable odds.